PENINGKATAN KESADARAN MASYARAKAT TENTANG WISATA ALAM, WAWASAN MINAT BELAJAR DAN KEBERSIHAN LINGKUNGAN DI DESA PARIKSABUNGAN SIMALUNGUN - Regina Sidabutar; Rosianna Siahaan; Sabta Sitinjak; Hardian Simanjuntak; Berkat Zai; Wiwin Zega; Mario Simbolon; Andres Gea; Fajar Telaumbanua; Kajian Daeli; Rizki Sipayung (Jurnal Abdimas Bina Bangsa, 2024)
Student Practical Work and Service aim to serve themselves to society and help deal with the problems they face in the hope of being able to apply the knowledge gained through the education process on campus. The UHN Research and Community Service Institute (LPPM) formed and provided the KPPM 47 program as a form of contribution in advancing general welfare and can make the nation's life more intelligent. KPPM Period 47 will be held on 05 February – 24 February 2024, in Simalungun district, Dolok Pardamean sub-district, especially Pariksabungan village. In carrying out this activity, students are expected to be able to help the area and its residents to develop the economy, preserve culture, and improve the welfare of society as a whole. The application method in implementing KPPM 47 is based on the results of field observations in Pariksabungan village, interviews and literature study. There are several activity programs carried out by students in the form of improving facilities and cleanliness at the Pinus Hills tourist attraction, reducing waste at the Tekosima natural tourist attraction on both sides of the road to Bukit Indah Simarjarunjung, teaching staff and additional/extracurricular classes in Mathematics and English at SDN 091401 and cleaning activities. at the Pariksabungan village office. The results of this research are: 1) Improving the facilities and cleanliness of the natural tourist attractions in Pariksabungan village, 2) Increasing and broadening the knowledge of students' interest in learning at SDN 191401 Pariksabungan, 3) Increasing public awareness in reducing waste at the natural tourist attractions of Tekosima to Bukit Indah Simarjarunjung. 4) Increasing good cooperation between students and Pariksabungan Village Government Apparatus through cleaning activities at the Pariksabungan village office